Advances in transition metal dichalcogenide-based two-dimensional nanomaterials. (March 2021) - Monga, Divya; Sharma, Surbhi; Shetti, Nagaraj P.; Basu, Soumen; Reddy, Kakarla Raghava; Aminabhavi, Tejraj M.
Abstract: Two-dimensional transition metal dichalcogenides (TMDCs) are the layered materials that have gained substantial consideration in a wide range of applications. The TMDCs possess exceptional properties such as high surface-to-volume ratio, excellent charge transfer capacity, mechanical strength, and low bandgap energy. Additionally, TMDCs (MoS2, WS2, etc.) are abundant, have a low synthesis cost, and are visible-light-active. The appealing surface morphologies and properties of TMDCs make them an appropriate choice for diverse applications like photocatalytic degradation of hazardous pollutants, energy conversion reactions (electrocatalytic and photocatalytic H2 production), and energy storage devices (supercapacitors and rechargeable batteries) in addition to bio/chemical sensors. This article addresses the latest trends and advancements in the domain of TMDC-based nanomaterials. The different synthesis routes have been comprehensively reviewed. The challenges faced by TMDCs at a large scale and the future scope have also been discussed. Graphical abstract: Image 1 Highlights: Recent advancements in the field of 2D-TMDCs were thoroughly reviewed. TMDCs manifest excellent activity in photocatalysis and electrocatalysis. TMDCs act as energy storage devices: supercapacitors and rechargeable batteries. The application of TMDCs in bio/chemical sensing was comprehensively discussed. Key challenges and future scopes in the applications were highlighted.